A Prediction of Solar Cycle Maxima Using Visibility Graphs - Eduardo Flández; Víctor Muñoz (The Astrophysical Journal)
We apply a complex network approach to analyze the time series of five solar parameters, and propose a strategy to predict the number of sunspots for the next solar maximum, and when this maximum will occur. The approach is based on the visibility graph (VG) algorithm, and a slightly modified version of it, the horizontal VG, which maps a time series into a complex network. Various network metrics exhibit either an exponential or a scale-free behavior, and we find that the evolution of the characteristic decay exponents is consistent with variations of the sunspot number along solar cycles. During solar minimum, the sunspot number and the F10.7 cm radio flux time series have characteristic decay exponents that correlate well with the next maximum sunspot number, suggesting that they may be good precursors of the intensity of the next solar maximum.